"Hybrid psychology agent": Overcoming the about/for dichotomy from praxis. (June 2020) - Macías-Gómez-Estern, Beatriz
I draw on my experience in community development with "othered" groups to present the idea of the "hybrid psychology agent." This, I contend, is a key figure in overcoming the dichotomies alleged by Indigenous psychologists and confronted by Held (2020). On the one hand, the concept is rooted in hands-on work in multicultural settings. It is also supported by Cultural-Historical research through projects such as Service Learning that connect higher education students with disenfranchised Roma children. On the other hand, the concept follows a critical theory framework where, as implied by Held, a paradigm shift in science is needed. The issue at point is not whether folk Indigenous knowledge should replace so-called objective knowledge, but how the latter should embrace the experience of a more diverse psychological object and subject, mainly through the participation of "othered" people as psychology scientists and practitioners.